2015
DOI: 10.1186/s13068-014-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy and African transformation

Abstract: Among the world’s continents, Africa has the highest incidence of food insecurity and poverty and the highest rates of population growth. Yet Africa also has the most arable land, the lowest crop yields, and by far the most plentiful land resources relative to energy demand. It is thus of interest to examine the potential of expanded modern bioenergy production in Africa. Here we consider bioenergy as an enabler for development, and provide an overview of modern bioenergy technologies with a comment on applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…Agricultural wastes and forest residues are the most promising biomass feedstocks for their abundance and relatively low cost [5]. Traditional use of lignocellulosic biomass has been limited to burning for cooking and heating, which lead to significant negative environmental impacts such as land degradation and desertification [6]. By means of thermochemical or biochemical conversion routes, lignocellulosic biomass can be converted into energy or energy carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural wastes and forest residues are the most promising biomass feedstocks for their abundance and relatively low cost [5]. Traditional use of lignocellulosic biomass has been limited to burning for cooking and heating, which lead to significant negative environmental impacts such as land degradation and desertification [6]. By means of thermochemical or biochemical conversion routes, lignocellulosic biomass can be converted into energy or energy carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Bioenergy can foster social development, which is a precondition for food security and sustainability. Bioenergy provides energy security not only for transport (and hence broader access to food, selling markets, employment, and services) but also for food processing, business development, and drying and storage of surplus production (Durham et al, 2012;Lynd et al, 2015). The latter, providing an outlet for surplus, diversifies sources of income and improves supply resilience in the event of market shocks or shortages.…”
Section: Two-way Linkagesmentioning
confidence: 99%
“…Recently, Lynd's team investigated the ability of six thermophilic microorganisms to breakdown switchgrass into soluble products, 3 which could then be fermented and ultimately used as fuel. The researchers showed that Clostridium thermocellum was twice as effective at breaking down switchgrass as the fungal enzymes currently used by industry.…”
Section: Hot Fuelsmentioning
confidence: 99%